Quantification of Organic Carbon Sequestered by Biogenic Iron Sulfide Minerals in Long-Term Anoxic Laboratory Incubations - Nabeh, Nader; Brokaw, Cheyenne; Picard, Aude (Frontiers in Microbiology, 2022)
Organic carbon sequestration in sedimentary environments control oxygen and carbon dioxide concentrations in the atmosphere. While minerals play an important role in the preservation of organic carbon, there is a lack of understanding about the formation and stability of organo-mineral interactions in anoxic environments, especially those involving authigenic iron sulfide minerals. In this study, we quantified organic carbon and nitrogen sequestered in biogenic iron sulfide minerals co-precipitated with sulfate-reducing bacteria (SRB) in freshwater and marine conditions in long-term laboratory experiments. The amounts of C and N associated with biogenic iron sulfide minerals increased with increasing cell biomass concentrations available in the media. C and N levels stabilized over the first 2 months of incubation, and remained stable for up to one year. Crystalline mackinawite (FeS) formed in all experimental conditions, and transformed to greigite only in some experimental conditions. We did not have evidence that this mineral transformation affected C and N levels, neither could we identify the factors that controlled greigite formation. Pyrite did not form in our experimental conditions. While C concentrations in minerals correlated with concentrations of reduced sulfate in both the freshwater and marine media, removal of OC by iron sulfide minerals was more efficient in freshwater than marine conditions. Removal of OC by iron sulfide minerals was also more efficient when cells were present (SRB biomass) in comparison to abiotic incubations with organic mixtures (e.g. tryptone, yeast extract and casamino acids) in abiotic incubations. Our study highlights the potential for iron sulfide minerals to quantitatively contribute to organic carbon preservation in anoxic environments.